Digital Transformation in Local Governance: Lessons from Pasuruan City’s E-Sambat Application - Khumaidi Khumaidi; Aminullah (Yayasan Ghalih Pelopor Pendidikan, 2025)
This study investigates how digital transformation shapes public service effectiveness through the implementation of the E-Sambat application in Pasuruan City, Indonesia. While e-government initiatives are increasingly promoted to enhance efficiency and citizen engagement, the role of digital leadership in sustaining these efforts remains underexplored. Using a qualitative case study, data were collected through interviews, observations, and document analysis. The findings reveal that E-Sambat has improved accessibility, responsiveness, and accountability, yet challenges persist, including low digital literacy, fragmented systems, and uneven infrastructure. Public servants emphasized the need for stronger leadership commitment and capacity building, while citizens highlighted both convenience and barriers in navigating digital platforms. The study contributes by demonstrating how digital leadership fosters innovation and adaptability in local governance, offering practical implications for municipalities seeking to strengthen service delivery through e-government.